2016
DOI: 10.1038/nnano.2016.30
|View full text |Cite
|
Sign up to set email alerts
|

Single-nanowire photoelectrochemistry

Abstract: Photoelectrochemistry is one of several promising approaches for the realization of efficient solar-to-fuel conversion. Recent work has shown that photoelectrodes made of semiconductor nano-/microwire arrays can have better photoelectrochemical performance than their planar counterparts because of their unique properties, such as high surface area. Although considerable research effort has focused on studying wire arrays, the inhomogeneity in the geometry, doping, defects and catalyst loading present in such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
92
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 30 publications
(12 reference statements)
1
92
0
Order By: Relevance
“…The NW-to-NW fluctuations in series resistance lead to broad range in current density between them, resulting in preventing some of the NWs to emit light. Also, in the use of NWs for photoelectrochemistry experiments, it was observed that the photovoltage of the NW array photoelectrode is highly affected by the worst-performing NW [36]. Our original approach here consists of addressing some of these issues in our devices in a more systematic way by C-AFM.…”
Section: Standard Nw Solar Cell Characterizationmentioning
confidence: 99%
“…The NW-to-NW fluctuations in series resistance lead to broad range in current density between them, resulting in preventing some of the NWs to emit light. Also, in the use of NWs for photoelectrochemistry experiments, it was observed that the photovoltage of the NW array photoelectrode is highly affected by the worst-performing NW [36]. Our original approach here consists of addressing some of these issues in our devices in a more systematic way by C-AFM.…”
Section: Standard Nw Solar Cell Characterizationmentioning
confidence: 99%
“…Substantially research efforts have been invested into the synthesis of these 1D materials, which allow for exquisite controls of composition, morphology, heterostructures, and reactivity 28, 29. The capability of modulation the composition and doping, either radially or even longitudinally, even within a single 1D nanostructure has been explicitly demonstrated 30, 31.…”
Section: Introductionmentioning
confidence: 99%
“…The capability of modulation the composition and doping, either radially or even longitudinally, even within a single 1D nanostructure has been explicitly demonstrated 30, 31. Thus, these achievements have also brought substantial advances and breakthroughs in the applications of utilization of 1D materials in almost all fields of modern technologies,29, 32, 33, 34 including the water splitting electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Special focus will be set on wireshaped nanostructures due to their potential applications in circuits or nanodevices [5,6], as membranes [7], biosensors [8][9][10], transparent electrodes [11], waveguides [12] or antennae in photochemistry [13].…”
Section: Introductionmentioning
confidence: 99%